Microscopic colitis in Northern Ireland: an updated clinicopathological audit and assessment of compliance with European guidelines. (31st July 2022) - Moore, Michelle; Coleman, Helen G.; Allen, Patrick B.; Loughrey, Maurice B.
Abstract: Aim: We previously reported the first population‐based study of the epidemiology of microscopic colitis in Northern Ireland. The aim of the current study is to provide updated data on incidence, diagnostic methods and clinicopathological associations, following dissemination of the previous report. A further aim was to compare the findings against relevant recommendations from the 2020 European guidelines. Method: Study cases were identified via the Belfast Health and Social Care Trust pathology laboratory system for new cases of collagenous colitis or lymphocytic colitis diagnosed from 2017 to 2020 inclusive. Demographic and clinical information was collated from electronic healthcare records. Results: Two hundred and seventeen new diagnoses of microscopic colitis were made between 2017 and 2020, comprising 89 (41%) collagenous colitis and 128 (59%) lymphocytic colitis. The overall incidence of microscopic colitis, expressed per 100, 000 adult population, ranged from 7.6 to 11.5 (5.9 to 9.0 per 100, 000 total population). The 2019 peak of 11.5 cases per 100, 000 adult population represents a 71.6% increase in incidence compared with the mean incidence of 6.7 per 100, 000 adult population from previous data for 2008–2016. There has also been a significant increase in number of cases diagnosed on separate sampling from the right and left colon (85% in 2019–2020 compared with 30% in 2008–2016; p  < 0.001). Overall compliance with coeliac serology testing has improved, with 89% tested in 2017–2018 compared with 75% in 2008–2016. Conclusion: Clinicopathological communication has contributed to an increased incidence of microscopic colitis in Northern Ireland through better endoscopic diagnostic sampling and pathology coding practices. Coeliac serology testing has also improved, although continued clinical awareness is required of the need for coeliac serology testing in all patients diagnosed with microscopic colitis.